2009
DOI: 10.1007/s11581-009-0400-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sm3+ ion in structural, morphological, and electrochemical properties of LiMn2O4 synthesized by microwave calcination

Abstract: LiSm x Mn 2-x O 4 samples were synthesized via coprecipitation technique. The structural properties of the synthesized materials were studied using X-ray diffraction analysis and it confirmed the cubic spinel structure for all the compounds. The lattice parameter of LiMn 2 O 4 was observed to be 8.2347 Ǻ and it decreased with Sm 3+ concentration, due to the shrinkage in cell volume aided by higher binding energy between Sm-O bond. The SEM micrographs were analyzed using Image processing software (Image-J) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 27 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…Nd doped LiMn 2 O 4 by chemical precipitation and calcination was researched by Singhal and Das [21], who reported that LiNd 0.01 Mn 1.99 O 4 has the highest discharge capacity (149 mA hg −1 ) and has a capacity retention of about 91% after 25 cycles. Balaji and Mutharasu [22] …”
Section: Introductionmentioning
confidence: 99%
“…Nd doped LiMn 2 O 4 by chemical precipitation and calcination was researched by Singhal and Das [21], who reported that LiNd 0.01 Mn 1.99 O 4 has the highest discharge capacity (149 mA hg −1 ) and has a capacity retention of about 91% after 25 cycles. Balaji and Mutharasu [22] …”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, the method is not used alone, but rather more than one method [44] is used in a preparation.…”
Section: Other Methodsmentioning
confidence: 99%
“…The common raw materials used are carbonates [22,78], acetates [79], nitrates [44,71], sulfates [80], hydroxides [73], oxides [81] of Li, Mn and the doped-ion. The preparation processes are various.…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substitution increases the average oxidation state of Mn above 3.5, and hence, suppressing Jahn-Teller distortion, stabilizes the crystal structure of the spinel. All dopant elements are less or close to that of Mn, but few reports about the rareearth elements have been published [30][31][32][33][34][35]. Here, we aim to go further and use uranium for metal substitution of LiMn 2 O 4 spinel.…”
Section: Introductionmentioning
confidence: 99%